AN INVESTIGATION OF TEACHER-STUDENT VERBAL INTERACTION IN AN INDONESIAN EFL CLASSROOM: A FLANDERS INTERACTION ANALYSIS CATEGORY (FIAC) SYSTEM - Ainun Pratiwi; Rahmah Fithriani (JOURNAL OF LANGUAGE, 2023)
This study aims to investigate the nature and extent of classroom interactions using the Flanders Interaction Analysis Category System (FIACS), a valuable tool for identifying, classifying, and monitoring verbal interaction in educational contexts. Specifically, the study seeks to analyze the interaction patterns between teachers and students, as well as the role of teachers in a public senior high school located in Medan, Indonesia. Participants in this qualitative inquiry included 36 eleventh-grade students and an English teacher. Utilizing an observation tally sheet, video recording, and interviews with the teacher and some students, the data were collected on the conversation between teacher and students during two 60-minute class meetings. The results reveal that the interactions that occur in the EFL class comprise a sum of 10 FIAC components. The pattern of interactions between teacher and students in the classroom is characterized by two-way communication. During classroom interaction, the role of the teacher encompasses that of a motivator, organizer, and prompter.